Cryotherapy as an adjuvant in the treatment with vismodegib for local advanced nonsurgical basal cell carcinoma: a report of 8 cases (2021)
Introduction: Basal cell carcinoma (BCC) is the most prevalent skin cancer worldwide. The most frequently used treatment for BCC is surgical resection. Lately, there are other options for nonsurgical BCC such as hedgehog pathways inhibitors, which is indicated in patients whose cancer is locally advanced and unresectable. We described the response of patients treated with vismodegib and cryotherapy as adjuvant management. Materials and methods: We conducted an observational retrospective study in a dermatologic center in Bogota, Colombia. We included patients with BCC diagnosis and were treated with vismodegib and cryotherapy from January 2018 to August 2020. Variables included age, sex, phototype, lesion location, treatment duration, number of cryotherapies, months of follow-up, and histologic subtypes. Variables were analyzed using Microsoft Excel 2016. Results: Of eight patients reviewed, four were female. Median age was 70 years old. Photoype III was the most frequent. Zone H was the most affected location. The mean number of cryotherapy sessions received during vismodegib treatment was 4.75, and the mean duration of treatment with the hedgehog inhibitor was 3.5 months. Patients were followed up for 15.57 months. Of the eight patients, four presented nodular pattern histology, in the rest the mixed subtype predominated. Conclusion: In general, there was a good response to treatment with a notable decrease in the size and control of the lesions. No side effects were described during the follow-up time; however, the patients will continue to be under strict controls.